2000
DOI: 10.1111/0026-7902.00049
|View full text |Cite
|
Sign up to set email alerts
|

The Complexity of Immersion Education: Teachers Address the Issues

Abstract: The purpose of this study was to enlist practitioners in language immersion programs in the identification and elaboration of issues and challenges in immersion language teaching. Through focus groups and extensive individual interviews, 6 elementary Spanish-language immersion teachers in 3 school settings (a suburban full-immersion school and 2 inner-city magnet programs-1 partial and 1 full immersion) served as informants. Five major themes emerged: the primacy of language, the balance between language and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
32
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(36 citation statements)
references
References 36 publications
4
32
0
Order By: Relevance
“…When English is the MoI, not only is it essential for teachers to help their learners to achieve mastery of specific linguistic skills such as reading, writing, listening and speaking (Arkoudis, 2003;Uys, van der Walt, van der Berg & Botha, 2007), it is the role of all teachers to be able to promote effective literacy skills across the entire curriculum regardless of the content or discipline area that they are specifically teaching (Goodwyn & Findlay, 2003;Uys et al, 2007). Teachers of disciplines other than the English language must also be able to use English to effectively deliver content knowledge to their students (Walker & Tedick, 2000;Othman & Mohd Saat, 2009). They therefore need to be highly proficient in the English language themselves in order to deliver their specialised content area in English (Othman & Mohd Saat, 2009).…”
Section: Review Of Literaturementioning
confidence: 99%
“…When English is the MoI, not only is it essential for teachers to help their learners to achieve mastery of specific linguistic skills such as reading, writing, listening and speaking (Arkoudis, 2003;Uys, van der Walt, van der Berg & Botha, 2007), it is the role of all teachers to be able to promote effective literacy skills across the entire curriculum regardless of the content or discipline area that they are specifically teaching (Goodwyn & Findlay, 2003;Uys et al, 2007). Teachers of disciplines other than the English language must also be able to use English to effectively deliver content knowledge to their students (Walker & Tedick, 2000;Othman & Mohd Saat, 2009). They therefore need to be highly proficient in the English language themselves in order to deliver their specialised content area in English (Othman & Mohd Saat, 2009).…”
Section: Review Of Literaturementioning
confidence: 99%
“…A study of 181 teachers across 12 different TWI programs found that, although they were largely supportive of the goals of this model, they found the work very labor-intensive (Howard & Loeb 1998). Teachers also indicated that they faced frequent tensions with parents regarding whether their children were receiving sufficient instruction in subject content, given the focus on second language acquisition (Howard & Loeb 1998;Walker & Tedick, 2000). Tensions with administrators have also been identified and focused on the need for additional resources for classroom instruction (Howard & Loeb 1998).…”
Section: Continuing Challenges Of Two-way Immersionmentioning
confidence: 99%
“…Despite the centrality of teachers' voice in the introduction and implementation of change, little research has examined teacher perspective on the use of integrated language and content instruction. Walker and Tedick (2000) pointed out that most of the research on bilingual education has addressed student language and learning issues, like the extent to which students are learning content through the L2 and how far they are learning the L2 through this approach. They contended that when research has focused on the teacher, it explored teacher classroom discourse, error treatment, and the extent to which teachers focus on the integration of language and content instruction: 'Little effort has been made to enlist practitioners in the identification and elaboration of issues, problems, and outcomes related to immersion language education.…”
Section: Teachers' Perspective and Education Changementioning
confidence: 99%
“…Another interviewed teacher added that some of the teachers are 'required to take language courses offered by the British Council in collaboration with the Supreme Education Council' in order to improve their English proficiency. Teachers' low proficiency in English is a challenge that has often been expressed in studies investigating teachers' attitudes to teaching content through a second language (Walker and Tedick 2000).…”
Section: Language Handicapmentioning
confidence: 99%